BAURU GROUP (LATE CRETACEOUS) VERTEBRATES FROM TRIÂNGULO MINEIRO - Carlos Roberto dos Anjos Candeiro (Sociedade & Natureza)
The Triângulo Mineiro (Minas Gerais State) and western São Paulo State have a rich and diversefauna of Late Cretaceous vertebrates from Adamantina, Uberaba and Marília formations (BauruGroup). This paper attempts to list the vertebrate fauna known from each formation within theTriângulo Mineiro region and western São Paulo using the most recent and accepted definition foreach formation or higher taxonomical group. The faunal list produced now gives us a clearerunderstanding of the stratigraphical distribution of the Bauru Group vertebrates.